1989
DOI: 10.1159/000185391
|View full text |Cite
|
Sign up to set email alerts
|

Polyarteritis Nodosa and Necrotizing Glomerulonephritis Associated with Long-Standing Silicosis

Abstract: A 55-year-old white male, with silicosis diagnosed 10 years earlier, presented massive proteinuria with microscopic hematuria, moderate renal failure and distal polyneuropathy. Bilateral renal angiography showed multiple intraparenchymal saccular aneurysms. Renal biopsy disclosed a focal segmental necrotizing glomerulonephritis and arteriolitis. After combined corticosteroid and immunosuppressive treatment, renal function improved and remained stable 6 months later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…25 It is worth noting that two linked papers on Spanish workers who cleaned silica flour showed extraordinarily high risks of autoimmune diseases, and two workers (of 50 examined) had glomerulonephritis-one with systemic lupus erythematosus, and the other without anyautoimmunedisease. 26 27 Inthiscontext,polyarteritis and necrotising glomelonephritis associated with silicosis has already been reported, 28 a condition similar to that which was found for patient 5 in our study.…”
Section: Discussionsupporting
confidence: 82%
“…25 It is worth noting that two linked papers on Spanish workers who cleaned silica flour showed extraordinarily high risks of autoimmune diseases, and two workers (of 50 examined) had glomerulonephritis-one with systemic lupus erythematosus, and the other without anyautoimmunedisease. 26 27 Inthiscontext,polyarteritis and necrotising glomelonephritis associated with silicosis has already been reported, 28 a condition similar to that which was found for patient 5 in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Animal studies have demonstrated that silica ca n produce a dose-related nephropath y that is primarily tubular and is ass ociated with inter stitial inflamma tory rea cti on s and fibrosis ( I, 2) . Several ca ses of nephropathy in workers exposed to silica ha ve been reported (3)(4)(5)(6)(7)(8)(9). The nephropathy has usually consis ted of a focal or seg mental, rapidly progressi ve glomerulonephritis without sig nific ant immune-complex deposits and with variable degrees of tubular degeneration.…”
mentioning
confidence: 99%
“…The most frequently reported autoimmune diseases were scleroderma, systemic lupus erythematosus (lupus), rheumatoid arthritis, autoimmune hemolytic anemia [Muramatsu et al 1989], and dermatomyositis or dermatopolymyositis [Robbins 1974;Koeger et al 1991]. Case reports have also described health effects such as the following that may be related to the immunologic abnormalities in patients with silicosis: chronic renal disease [Saita and Zavaglia 1951;Bolton et al 1981;Giles et al 1978;Pouthier et al 1991;Neyer et al 1994;Dracon et al 1990;Sherson and Jorgensen 1989;Rispal et al 1991;Osorio et al 1987;Bonnin et al 1987;Arnalich et al 1989;Wilke et al 1996;Banks et al 1983;Hauglustaine et al 1980;Slavin et al 1985], ataxic sensory neuropathy [Tokumaru et al 1990], chronic thyroiditis [Masuda 1981], hyperthyroidism (Graves'disease) [Koeger et al 1996], monoclonal gammopathy [Fukata et al 1983[Fukata et al , 1987Aoki et al 1988], and polyarteritis nodosa [Arnalich et al 1989]. …”
Section: Autoimmune and Chronic Renal Diseasesmentioning
confidence: 99%